PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI MODEL INQUIRY BASED LEARNING BERBANTUAN KARTU CERDAS MATEMATIKA PADA SISWA SEKOLAH DASAR - Friska Yolanda Lase, Elkin; Roestika Rini, Zulmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of the Inquiry Based Learning learning model assisted by Mathematics Smart Cards on the problem-solving abilities of third-grade elementary school students. This study uses a quantitative method with a Quasi Experimental Design method. The population in this study were all students of SDN Harjosari 01, with a sample of class III A of 26 students as the experimental class and class III B of 27 students as the control class. Data collection techniques were carried out through test techniques (pretest and posttest) and non-test (observation, interviews, and documentation). The results of the study showed that: (1) there was a significant difference based on the results of the Independent Sample t-test with a significance value of 0.015 < 0.05; (2) the Inquiry Based Learning learning model assisted by Mathematics Smart Cards had a significant influence on students' problem-solving abilities based on the results of a simple linear regression test with a significance value of 0.015 < 0.05; and (3) the Inquiry Based Learning learning model assisted by Mathematics Smart Cards effectively improved students' problem-solving abilities. This is demonstrated by the average posttest score (0.384) in the experimental class, which was higher than the posttest score (0.293) in the control class. Based on the research results, it can be concluded that the Inquiry-Based Learning model assisted by Mathematics Smart Cards is effective in improving student problem-solving.